Developing a modified directly observed therapy intervention for hepatitis C treatment in a methadone maintenance program: implications for program replication. - Bruce, R Douglas; Eiserman, Julie; Acosta, Angela; Gote, Ceilia; Lim, Joseph K; Altice, Frederick L (The American journal of drug and alcohol abuse, 2012)
Hepatitis C virus (HCV) is a prevalent chronic blood-borne infection among opioid-dependent patients on methadone maintenance treatment (MMT). Despite case reports and case-control studies, a randomized controlled trial (RCT) examining HCV treatment adherence in methadone-maintained patients is lacking and was the impetus for this ongoing RCT examining modified directly administered therapy for HCV treatment integrated within a MMT.
Keywords: Adult; Antiviral Agents; Directly Observed Therapy; Female; Hepacivirus; Hepatitis C; Humans; Interferon-alpha; Male; Medication Adherence; Methadone; Middle Aged; Opiate Substitution Treatment; Opioid-Related Disorders; Pilot Projects; Polyethylene Glycols; Recombinant Proteins; Ribavirin; Self Administration; Viral Load